2004
DOI: 10.1189/jlb.1203621
|View full text |Cite
|
Sign up to set email alerts
|

HCMV activates PI(3)K in monocytes and promotes monocyte motility and transendothelial migration in a PI(3)K-dependent manner

Abstract: Human cytomegalovirus (HCMV) is a leading cause of morbidity and mortality in immunocompromised hosts. In immunocompetent hosts, HCMV is associated with chronic inflammatory diseases including atherosclerosis. Monocytes and macrophages are proposed to play key roles in HCMV dissemination to host tissue, and their infection provides a biological link between the lifecycle of HCMV and disease pathology. We hypothesize that viral spread occurs via a mechanism in which infected peripheral blood monocytes, which ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
139
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(154 citation statements)
references
References 72 publications
14
139
1
Order By: Relevance
“…Our data suggest that MCL-1 is an attractive target for the establishment of latency. Interestingly, HCMV has also been shown to activate the PI3K pathway in both permissive (10) and nonpermissive infection (40), which suggested that the protective effects of HCMV we observed could be mediated via this pathway also. Although we cannot preclude a role for the activation of these pathways in aspects of cell survival, in our hands, it was the ERK pathway that appeared important for initial survival of latently infected CD34 + cells in response to infection or the further stress of cisplatin A. Interestingly, the pathogenesis of chronic myeloid leukemia has also been associated with the activation of MCL-1 expression in an ERK-, but not PI3K-, dependent manner consistent with ERK-induced activation of MCL-1 being important for early myeloid cell survival (41).…”
Section: Discussionmentioning
confidence: 80%
“…Our data suggest that MCL-1 is an attractive target for the establishment of latency. Interestingly, HCMV has also been shown to activate the PI3K pathway in both permissive (10) and nonpermissive infection (40), which suggested that the protective effects of HCMV we observed could be mediated via this pathway also. Although we cannot preclude a role for the activation of these pathways in aspects of cell survival, in our hands, it was the ERK pathway that appeared important for initial survival of latently infected CD34 + cells in response to infection or the further stress of cisplatin A. Interestingly, the pathogenesis of chronic myeloid leukemia has also been associated with the activation of MCL-1 expression in an ERK-, but not PI3K-, dependent manner consistent with ERK-induced activation of MCL-1 being important for early myeloid cell survival (41).…”
Section: Discussionmentioning
confidence: 80%
“…3B). Pretreatment with the DMSO solvent control (3,5) or the IgG isotype-matched control did not affect HCMV-induced motility. Similar results were observed when EGF was used as the activating ligand, further supporting the role that EGFR plays in directly modulating monocyte motility (Fig.…”
Section: Hcmv Promotes Monocyte Motility and Transendothelial Migratimentioning
confidence: 99%
“…The 2.5-fold induction in transendothelial migration by HCMV or EGF was abrogated by inhibition of EGFR signaling. Pretreatment with the DMSO solvent control (3,5) or the IgG isotype-matched control antibody did not affect HCMV-induced monocyte transendothelial migration. Together, these data show that EGFR possesses biological functions in human peripheral blood monocytes and are consistent with our hypothesis that EGFR engagement by the virus triggers changes in monocytes to promote hematogenous dissemination.…”
Section: Hcmv Promotes Monocyte Motility and Transendothelial Migratimentioning
confidence: 99%
See 1 more Smart Citation
“…The precise function of UL128 on host immune cells remains unknown. Recent evidence shows that HCMV may upregulate cellular gene products associated with monocyte extravasation and inflammation, such as adhesion molecules, inflammatory cytokines, chemokines, and chemokine receptors in a PI(3)K-dependent manner (13,14). Our objective was to determine if HCMV-encoded UL128 interferes with the initiating steps in the host immune response, or if it modulates the function of host inflammatory cells.…”
Section: Introductionmentioning
confidence: 99%